Cover Feature: Sulfur Dioxide Capture in Metal‐Organic Frameworks, Metal‐Organic Cages, and Porous Organic Cages (ChemPlusChem 6/2022). Issue 6 (26th April 2022) - Gupta, Nishesh Kumar; López‐Olvera, Alfredo; González‐Zamora, Eduardo; Martínez‐Ahumada, Eva; Ibarra, Ilich A.
Abstract : The cover feature image illustrates sulphur dioxide adsorption on three types of porous material: metal organic frameworks (MOFs), metal organic cages (MOCs), and porous organic cages (POCs), represented by sky lanterns. Each of the materials has advantages and disadvantages as SO2 adsorbents, which are discussed in this Review article, but without doubt all of them are needed as part of the global effort to mitigate the release of this polluting gas. Cover design by Alfredo López‐Olvera and Eva Martínez‐Ahumada. More information can be found in the Review by E. Martínez‐Ahumada, I. A. Ibarra and co‐workers .